SOCIAL CAPITAL AS A STIMULANT FOR THE DEVELOPMENT OF ENTERPRISES IN THE PODKARPACKIE PROVINCE - Ślusarczyk, Bogusław; Dziura, Bernadetta (Proceedings of the International Scientific Conference "Economic Sciences for Agribusiness and Rural Economy", 2018)
Social capital is one of the essential elements of an enterprise’s development. Enterprises with a high level of social capital, due to the smooth flow of information, are predisposed to achieve higher innovation, gaining an advantage over competitors (Przybysz, 2011). The social capital affects the creation of the unique value of an enterprise, mainly through the structures of the connections network, social and cultural norms as well as trust (Dziura, 2016). Nowadays, it is analysed at various levels and in varying degrees, also in relation to territorial systems, including the provincial level. The present paper is an attempt to analyse and describe the impact of social capital on development of selected enterprises in the Podkarpackie province. Authors of the article, due to the conducted surveys, application of statistical methods and analysis of financial reports, aim at presenting the effects of investing in social capital.